The law of treasure - Guest, Anthony Gordon; Matthews, Paul (Paul Bernard John) (Archaeopress Publishing Ltd, 2018)
This title aims to provide a reliable guide to the Law of Treasure in England, Wales and Northern Ireland. It will be of vital interest and utility to metal detectorists in addition to archaeologists, museums, coroner's offices, finds liaison officers, farmers and landlords' associations.